Exploration of dynamics in a complex person-centred intervention process based on health professionals' perspectives - Febe Friberg; Catarina Wallengren; Cecilia Håkanson; Eva Carlsson; Frida Smith; Monica Pettersson; Elisabeth Kenne Sarenmalm; Richard Sawatzky; Joakim Öhlén (BMC, 2018)
Abstract Background The assessment and evaluation of practical and sustainable development of health care has become a major focus of investigation in health services research. A key challenge for researchers as well as decision-makers in health care is to understand mechanisms influencing how complex interventions work and become embedded in practice, which is significant for both evaluation and later implementation. In this study, we explored nurses' and surgeons' perspectives on performing and participating in a complex multi-centre person-centred intervention process that aimed to support patients diagnosed with colorectal cancer to feel prepared for surgery, discharge and recovery. Method Data consisted of retrospective interviews with 20 professionals after the intervention, supplemented with prospective conversational data and field notes from workshops and follow-up meetings (n = 51). The data were analysed to construct patterns in line with interpretive description. Results Although the participants highly valued components of the intervention, the results reveal influencing mechanisms underlying the functioning of the intervention, including multiple objectives, unclear mandates and competing professional logics. The results also reveal variations in processing the intervention focused on differences in using and talking about intervention components. Conclusions The study indicates there are significant areas of ambiguity in understanding how theory-based complex clinical interventions work and in how interventions are socially constructed and co-created by professionals' experiences, assumptions about own professional practice, contextual conditions and the researchers' intentions. This process evaluation reveals insights into reasons for success or failure and contextual aspects associated with variations in outcomes. Thus, there is a need for further interpretive inquiry, and not only descriptive studies, of the multifaceted characters of complex clinical interventions and how the intervention components are actually shaped in constantly shifting contexts.